The correlation among language learning strategies, reading attitude, and reading achievement of the eleventh grade students in senior high schools - Intan Maulidasari; Tahrun Tahrun; Mulyadi Mulyadi (Journal of Educational and Learning Studies, 2021)
This study aimed to find out the correlation among language learning strategies, reading attitude, and reading achievement of the eleventh grade students of State Senior High Schools Lahat District. In this study, 85 students of the eleventh grade were chosen as sample through stratified random sampling. This study applied correlation research design. Questionnaire and test was used to collected the data. They were analyzed by using pearson product moment correlation coefficient, simple and multiple regression analysis. The result showed that the sig value of correlation between learning strategies and reading achievement was 0.04 which was higher than 0.05, with 5% contribution of learning strategies. The correlation between reading attitude and reading achievement was 0.000 which lower than 0.05, with 15.8% contribution of reading attitude. The correlation between learning strategies and reading attitude was 0.006 which was lower than 0.05, with 8.7% contributions. The correlation among language learning strategies, reading attitude, and reading achievement was 0.000 which was lower than 0.05, with 17% contributions of learning strategies and reading attitude.